Relationship between push phase and final race time in skeleton performance - Zanoletti, C.; La Torre, A.; Merati, G.; Rampinini, E.; Impellizzeri, F. M. (The Journal of Strength and Conditioning Research, 2006)
The aim of this study was to examine the relationship between push-time and final race time in skeleton participants during a series of major international competitions to determine the importance of the push phase in skeleton performance. Correlations were computed from the first and second heat split data measured during 24 men and 24 women skeleton competitions. Body mass, height, age, and years of experience of the first 30 men and women athletes of the skeleton, bobsleigh and luge 2003-2004 World Cup ranking were used for the comparison between sliding sports. Moderate but significant correlations (p < 0.05) were found between push-time and final race time in men (rmean = 0.48) and women (rmean = 0.63). No correlations were found between changes in the individual push-time between the first and second heat with the corresponding changes in final race time. The bobsleigh sliders are heavier than the athletes of the other sliding disciplines. Luge athletes have more experience and are younger than bobsleigh and skeleton sliders. The results of this study suggest that a fast push phase is a prerequisite to success in competition and confirms that the selection of skeleton athletes based on the ability to accelerate to a maximum speed quickly could be valid. However, a good or improved push-time does not ensure a placement in the top finishing positions. On the basis of these results, we suggest that strength and power training is necessary to maintain a short push-time but additional physical training aimed to enhance the push phase might not reflect performance improvements. The recruitment of younger athletes and an increase of youthful competitive activity may be another effective way to reach international competitive results.